PENGARUH KOMITMEN ORANG TUA MURID, MOTIVASI KERJA DAN IKLIM KERJA SEKOLAH TERHADAP PRODUKTIVITAS KERJA GURU SEKOLAH DASAR DI KECAMATAN IMOGIRI, KABUPATEN BANTUL TAHUN AJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Influence of Parents’ Comitment, Work Motivation and Work Atmosphere on Primary School Teacher Productivity in Imogiri District, Bantul Regency 2012/2013. The purpose of this research is to figure out the influence of parents’ commitment, work motivation and work atmosphere on Primary School teachers’ productivity in Imogiri District, Bantul Regency 2012/2013. The participants of the research are teachers of Primary School in Imogiri District from 22 schools, with the total participant 298. The sampel was taken154 teachers with a proportional random sampling. Nomogram Harry King formula was used to determine the total of the sample using 95% confident (5% of error standard) which was taken from 298 teachers. Techniques of data collection is by using questionnaires. The method used in this research in descriptive correlative with quantitative approach. The rules analysis test was normality test, linearity test and multicolinearity tested. The data analysis used are multiple regression analysis, F-test and partial correlation analysis. Determination coefficient analysis is used to find out effective contribution and relative contribution.The result of this research shows these following condition: (1) There is positive and significant influence among parents’ commitment, work motivation and school work atmosphere on Primary School teachers’ productivity in Imogiri District, Bantul Regency. Parents’ commitment contributes 46,70% effective contribution, followed school work atmosphere 16,80% and work motivation 4,20%. (2) There is a positive and significant influence of parents’ commitment toward Primary School teachers’ productivity in Imogiri District, (3) There is positive and significant influence of work motivation toward Primary School teachers’ productivity in Imogiri District, (4) There is a positive and significant influence of School work atmosphere toward teachers’ productivity in Imogiri District , Bantul Regency 2012/2013.